The effect of challenge-based learning on developing algebraic thinking skills among third-year middle school female students - Al-Fahd, Lulwah Abdullah; Al-Sharif, Khaled Mohammed (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to reveal the effect of challenge-based learning in developing algebraic thinking skills among third-year middle school students. The study used the quasi-experimental approach, through two equivalent experimental groups consisting of (32) students, and a control group consisting of (32) students. The experimental group studied using challenge-based learning, while the control group studied in the usual way. To verify the hypotheses, the algebraic thinking test tool was applied before and after to the research sample. The research found that The following results:There is a statistically significant difference at the significance level < (,01) between the average scores of the experimental group members and the average scores of the control group members in the post-test of the algebraic thinking test, and on the total score of the valid test of Experimental group.A set of recommendations and proposals were presented in light of the research procedures and in the results.
Keywords: challenge-based learning; algebraic thinking